Impact of Supplementary Nutrition on Undernourished Children In An Urban Area Of Meerut- A Longitudinal Study - Pandey, Gargi; Chopra, Harivansh; Bano, Tanveer; Jain, Seema; Singh, Ganesh (Indian Journal of Community Health, 2022)
Background: Infants and pre-school are most susceptible to undernutrition. Integrated Child Development Services is the programme focussing undernourished children by providing them supplementary nutrition. Aim& Objective: To study prevalence of undernutrition in 0-6 year old children and to study factors associated with it. To study impact of supplementary nutrition on undernourished children. Settings and Design: A longitudinal study. Methods and Material: The present longitudinal study was conducted in randomly selected Anganwadis of urban Meerut. Children found to be suffering from under nutrition were followed up at interval of six months to see the impact of supplementary nutrition provided to them at the anganwadi centre. A detailed history of relevant underlying factors responsible for causation of under nutrition were taken from mothers of these children. Statistical analysis used: chi square test was used to find out association between risk factors and undernutrition. Risk factor found statistically significant were further analysed using step wise multiple logistic regression analysis. The impact of supplementary nutrition was assessed using paired t test. Results: Iron folic acid supplementation during pregnancy, exclusive breast feeding in children, immunization and time of initiating complementary feed were found statistically significant on both chi-square and multiple logistic regression analysis. No impact of supplementary nutrition was found on anthropometric measurements of children. Conclusions: The main focus for fighting undernutrition in children (0-6 years) should be on preventing risk factors associated with mothers in antenatal period and during child rearing practices